Regulation of the tuft cell-ILC2 circuit in intestinal mucosal immunity - Shang, Kaiyu; Qi, Xinxin; Tian, Tingting; Shi, Huidong; Zhu, Yuejie; Zhang, Fengbo (Frontiers in Immunology, 2025)
The intestinal mucosal immune system maintains homeostasis through complex interactions between epithelial cells and innate lymphoid cells in the lamina propria. Tuft cells, previously overlooked intestinal epithelial cell types, detect parasites and metabolites via Sucnr1 and TAS2R receptors. They secrete IL-25, which activates type 2 innate lymphoid cell (ILC2) via the IL-25R receptor. ILC2 releases IL-13, resulting in further promotion of tuft and goblet cells from stem cells. This positive feedback loop amplifies the local type 2 immune response, combating parasitic infections. Tuft cells also recognize viruses and bacteria, but the role played by the tuft cell-ILC2 circuit in this process is not yet clear. Furthermore, tuft cell-ILC2 circuit is influenced by dietary fiber, intestinal microbiota, and other factors, contributing to new functions in maintaining intestinal homeostasis. In inflammatory bowel disease, this immunological circuit may be protective. This review summarizes the current understanding of the tuft cell-ILC2 circuit, its regulatory mechanisms, and potential implications in intestinal disease. Graphical abstract (by Figdraw 2.0)